Accuracy of echocardiography and chest tomography for pulmonary hypertension screening in patients awaiting lung transplantation - Degani-Costa,Luiza Helena (2021)
ABSTRACT Objective To examine the accuracy of a pulmonary hypertension screening strategy based on a combination of echocardiographic data and tomographic measurements (pulmonary artery diameter and pulmonary artery diameter to ascending aorta diameter ratio) in patients with chronic lung disease referred for lung transplantation. Methods A retrospective observational study with patients with pulmonary emphysema or fibrosis referred for transplantation between 2012 and 2016. Pulmonary hypertension was defined as mean pulmonary artery pressure ≥25mmHg, or between 21 and 24mmHg, with pulmonary vascular resistance >3 Wood units on right heart catheterization. Tomographic measurements were made by two independent radiologists. Results This sample comprised 13 patients with emphysema and 19 patients with pulmonary fibrosis. Of these, 18 had pulmonary hypertension. The level of agreement in tomographic measurements made by radiologists was high (intraclass correlation coefficients 0.936 and 0.940, for pulmonary artery diameter and pulmonary artery diameter to ascending aorta diameter ratio, respectively). Areas under the ROC curves constructed for pulmonary artery diameter, pulmonary artery diameter to ascending aorta diameter ratio, and pulmonary artery systolic pressure as predictors of pulmonary hypertension were 0.540, 0.629 and 0.783, respectively. The sensitivity, specificity and negative predictive value of pulmonary artery systolic pressure ≥40mmHg were 67%, 79% and 65%, respectively. The combined criterion (pulmonary artery diameter to ascending aorta diameter ratio >1 and/or pulmonary artery systolic pressure ≥40mmHg) achieved sensitivity of 72%, specificity of 79%, and a negative predictive value of 69%. Conclusion Measurements of pulmonary artery and ascending aorta diameter were highly reproducible. The association of pulmonary artery and aortic diameter >1 and/or pulmonary artery systolic pressure ≥40mmHg improved the sensitivity and the negative predictive value for pulmonary hypertension screening. This strategy demands prospective validation to assess safety and cost-effectiveness.